Estándares internacionales de la institucionalización de las personas con discapacidad mental aplicables a Colombia - Castillo Moreno, María Valentina Castillo Moreno; García Vergara, Jhon Alexander; Avendaño Sandoval, Alejandro (Uptc, 2022)
The object of this research is the institutionalization of the persons with mental disability, this device enjoys with the validation and acceptation from the social, cultural, medical and legal components for this reason, the present research has for general object to determinate what are the international standards of the institutionalization for people who has mental disabilities.And in order to develop this one, has been used the deductive and descriptive method because it starts since general, that means the most relevant concepts allied with the institutionalization and disability. To the particular, with the review of the international practice about the concretionary cases of mental disability. This one allowed to got as a result the vulneration of the juridical personality, personal integrity and health rights.For this reason, by means of show the imperious requirement for the international community and Estates to focus to the equality and equity in order to include and no discriminate the people with mental disability.